Human development and performance throughout the life span - Cronin, Anne; Mandich, MaryBeth (Boston, MA : Cengage Learning, 2016)
Human Development and Performance Throughout the Lifespan, 2nd Edition is ideal for occupational therapy, physical therapy, and other rehabilitation disciplines. It provides a broad, occupation-based viewpoint of development and performance throughout all life stages with an emphasis on the factors that influence daily participation and optimal performance of desired daily life tasks. The authors use a life course conceptual model as an organizational foundation for clinical reasoning to help readers understand how to implement the activity- and participation-based goals and outcomes for therapy. Written by an occupational therapist and a physical therapist, the book incorporates chapters by leading experts in human development, giving users cutting-edge information and a wide range of perspectives. By integrating information from the International Classification of Function and Disability (ICF) with a developmental life-task perspective, the book gives both newcomers and experienced professionals an essential, contemporary frame of reference.
pt. 3. Special topics in human development and performance. 21. Public policy and health care / Barbara L. Kornblau and Anne Cronin : Social justice ; Policy on an international scale ; National policy ; Antidiscrimination legislation ; Entitlement programs ; Health care policy ; Advocacy and political action ; Policy issues for rehabilitation professionals ; Telehealth ; Individuals with Disabilities Education Act (IDEA) ; Oh! The politics of health care! -- 22. Assessment of human performance across the lifespan / MaryBeth Mandich, Anne Cronin and Toby Long : Models of assessment ; Tests and measures ; Overview of common assessments by ICF dimension ; Assessment as a guide to treatment ; The ICF, health outcomes, and health policy ; Measuring the unmeasureable.
Includes bibliographical references and index.
Keywords: Disabled Persons -- rehabilitation; Activities of daily living; Human development; Occupational therapy -- methods